Quasi‐Solid‐State All‐V2O5 Battery - Wang, Guolong; Cui, Xiaoqian; Yang, Zhuofan; Liu, Jiamei; Shi, Xiaowei; Zhang, Yan; Zhao, Zehua; Wang, Jingqi; Song, Jiale; Wang, Xiao; Li, Yanhuai; Song, Zhongxiao; et al. (Small (Weinheim an der Bergstrasse, Germany), 2024)
Solid‐state symmetrical battery represents a promising paradigm for future battery technology. However, its development is hindered by the deficiency of high‐performance bipolar electrodes and compatible solid electrolytes. Herein, a quasi‐solid‐state all‐V2O5 battery constructed by a binder‐free carbon fabric‐V2O5 nanowires@graphene (CVOG) bipolar electrode and a softly cross‐linked polyethylene oxide‐based solid polymer electrolyte (SPE) is reported. The synergetic effect of nano‐structuring of V2O5, hierarchical conductive network, and graphene wrapping endows the CVOG electrode with boosted reaction kinetics and suppressed vanadium dissolution. The cathodic and anodic reactions of CVOG are decoupled by electrochemical analysis, conceiving the feasibility of constructing all‐V2O5 full battery. In manifesting the solid‐state all‐V2O5 battery, the robust and elastic SPE exhibits high ionic conductivity, tight/self‐adaptable electrolyte‐electrode contact, and a low charge‐transfer barrier. The resultant solid‐state full battery exhibits a high reversible capacity of 158 mAh g−1 at 0.1 C, good capacity retention of over 61% from 0.1 C to 2 C, and remarkable cycling stability of 77% capacity retention after 1000 cycles at 1 C, which surpass other solid‐state symmetrical batteries. Hence, this work provides a practice of high‐performance solid‐state batteries with symmetrical configuration and is constructive for next‐generation battery technology. A quasi‐solid‐state all‐V2O5 battery is demonstrated by using a binder‐free graphene‐wrapped V2O5 nanowires‐carbon fabric bipolar electrode and a cross‐linked polyethylene oxide‐based electrolyte. This battery shows a well‐defined discharge voltage plateau and excellent electrochemical performance in capacity, rate property, and cycling stability over other reported solid‐state symmetrical batteries.